2008
DOI: 10.1007/s10616-008-9155-y
|View full text |Cite
|
Sign up to set email alerts
|

A serum substitute for fed-batch culturing of hybridoma cells

Abstract: We developed a substitute for serum to produce fed-batch cultures of hybridoma cells in serum-free medium and confirmed that the cells could be successfully cultivated this way. Our substitute consisted of 12 components. The specific production rates of lactate and ammonia, which are harmful byproducts from the cells, were significantly reduced compared with a conventional serum-containing batch culture. This reduction led to a higher cell concentration and a longer production lifetime. As a result, the final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The mammalian cell culture medium normally contains pyruvate, but its concentration is low. Shibuya et al [22] reported that pyruvate is one of the 12 important components for serum substitute in fed-batch operation. Malate is an important intermediate from TCA cycle to pyruvate, which is a shuttle intermediate from the mitochondria TCA cycle to cytoplasmic glycolysis in hybridoma [16].…”
Section: Intermediate Addition In Continuous Culturementioning
confidence: 99%
“…The mammalian cell culture medium normally contains pyruvate, but its concentration is low. Shibuya et al [22] reported that pyruvate is one of the 12 important components for serum substitute in fed-batch operation. Malate is an important intermediate from TCA cycle to pyruvate, which is a shuttle intermediate from the mitochondria TCA cycle to cytoplasmic glycolysis in hybridoma [16].…”
Section: Intermediate Addition In Continuous Culturementioning
confidence: 99%
“…For example, Bai et al (31) demonstrated that the interaction of iron and citrate plays a role in up-regulating the protein synthetic machinery for promoting protein production. Vitamins such as vitamin B12, myo-inositol, niacinamide, and folic acid, are reported to be involved in cell growth pathways via fatty acid synthesis, energy production, intracellular calcium control, and re-dox regulation (9). Selenium has been shown to protect cells from oxidative damage by activating glutathione peroxidase or serving as an iron carrier (20,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies (mAbs) are commonly exposed to reducing sugars at different stages of the manufacturing process. 19 , 20 For example, high concentrations of glucose are usually added at the beginning of the cell culture process and supplemented intermittently as needed. Galactose may also be added to the cell culture medium to control the level of galactosylation.…”
Section: Introductionmentioning
confidence: 99%